The Influence of Volta Element-Based Learning Media on Students’ Science Process Skills - Sudirman Sudirman (Postgraduate, University of Mataram, 2023)
Based on the results of interviews with science subject teachers for class IX as initial observations at SMP Negeri 5 North Polongbangkeng, it was found that there were obstacles during the learning process in class where educators still played an active role in learning (middle teacher). Besides that, the facts found in class show that learning is less effective and enjoyable so students are less enthusiastic about learning, and only memorize concepts but applying these concepts in everyday life is still difficult. The purpose of this study was to increase students' abilities in scientific processes with voltaic media. The type of research used in this research is Quasi Experiment. The design of this study was (the matching only pretest-posttest control group design). Learning media based on voltaic elements is media that can utilize natural resources in the surrounding environment and specifically for science-based subjects, besides being able to increase students’ learning abilities and improve students' abilities and science process skills.